An integrated care solution for the electrocardiogram monitoring. Issue 1 (6th July 2020) - Chow, Josephine S.F.; Hopkins, Andrew; Dimitri, Hany; Tie, Hui; Williams, Rachael; Rajaratnam, Rohan; Gopinath, Sumana; Lazarovska, Suzana; Andrijevic, Stanica; Premawardhana, Upul; Gonzalez-Arce, Veronica E.; McDougall, Alan
Abstract : Purpose: This study has demonstrated how technology may contribute to integrated care solutions by comparing conventional ward telemetry (WT) to a wearable ECG monitor (S-Patch) to detect atrial fibrillation (AF) in patients with stroke. Design/methodology/approach: 51 patients admitted for stroke workup were recruited across two major tertiary centres to compare WT monitoring for two days versus S-Patch for four days in the detection of AF. The efficacy to detect AF using both technologies was assessed via data extractions and medical officer review. A matrix was used to measure nursing/patient satisfaction and setup/resource times were assessed. Findings: Patients (84–94%) and nursing staff (75–95%) preferred the S-Patch wearable technology. Non-parametric tests indicated significant time saving for removal of S-Patch versus WT [2.2 min vs 5.1 min ( p  = 0.00)]. Efficacy of S-Patch to detect AF following medical officer review was greater than WT, with seven patients identified with AF by S-Patch versus one using WT. The S-patch had a false positive rate of 78%. Research limitations/implications: The S-Patch is sensitive in the detection of AF; however, it showed a high false-positive rate with automated reporting. This study has provided insight into the details of delivery of integrated healthcare using wearable technology. Originality/value: The technology and partnership were the first-in-kind in Australia. The S-Patch had a higher detection rate of AF compared to WT which allows patients to be anti-coagulated appropriately for the prevention of further stroke. The results of this study will be ideally placed to inform future policy in integrated healthcare using new technologies.